Methodological Quality and Risk of Bias Assessment of Cardiovascular Disease Research: Analysis of Randomized Controlled Trials Published in 2017 - Baasan, Odgerel; Freihat, Omar; Nagy, David U.; Lohner, Szimonetta (Frontiers in Cardiovascular Medicine, 2022)
All RCTs are required to follow high methodological standards. In this study, we aimed to assess the methodological quality of published cardiovascular clinical research trials in a representative sample of RCTs published in 2017. Methods Cochrane Central Register of Controlled Trials was used to identify cardiovascular clinical research trials with adult participants published in 2017. Overall, 250 (10%) RCTs were randomly selected from a total of 2419 studies. Data on general trial characteristics were extracted and risk of bias (RoB) was determined. Results Overall, 86% have reported at least one statistically significant result, with the primary outcome significant in 69%, treatment favored in 55% and adverse events reported in 68%. Less than one-third (29%) of trials were overall low RoB, while the other two-thirds were rated unclear (40%) or with high RoB (31%). Sequence generation, allocation concealment and selective reporting were the domains most often rated high RoB. Drug trials were more likely to have low RoB than non-drug trials. Significant differences were found in RoB for allocation concealment and blinding of participants and personnel between industry-funded and non-industry-funded trials, with industry-funded trials more often rated at low RoB. Conclusion Almost two-thirds of RCTs in the field of cardiovascular disease research, were at high or unclear RoB, indicating a need for more rigorous trial planning and conduct. Prospective trial registration is a factor predicting a lower risk of bias.